ANALYTIC SIGNAL APPROACH AND ITS APPLICABILITY IN ENVIRONMENTAL MAGNETIC INVESTIGATIONS - Salem A.; Ravat D.; Gamey T.J.; Ushijima K. (My University, 2002)
We investigate the analytic signal method and its applicability in obtaining source locations of compact environmental magnetic objects. Previous investigations have shown that, for two-dimensional magnetic sources, the shape and location of the maxima of the amplitude of the analytic signal (AAS) are independent of the magnetization direction. In this study, we show that the shape of the AAS over magnetic dipole or sphere source is dependent on the direction of magnetization and, consequently, the maxima of the AAS are not always located directly over the dipolar sources. Maximum shift in the horizontal location is obtained for magnetic inclination of 30°. The shifts of the maxima are a function of the source-to-observation distance and they can be up to 30% of the distance. We also present a method of estimating the depths of compact magnetic objects based on the ratio of the AAS of the magnetic anomaly to the AAS of the vertical gradient of the magnetic anomaly. The estimated depths are independent of the magnetization direction. With the help of magnetic anomalies over environmental targets of buried steel drums, we show that the depths can be reliably estimated in most cases. Therefore, the analytic signal approach can be useful in estimating source locations of compact magnetic objects. However, horizontal locations of the targets derived from the maximum values of the AAS must be verified using other techniques.
Keywords: MAGNETIC; ANALYTIC SIGNAL; DEPTH ESTIMATION; ENVIRONMENTAL